Pre-analysis process for knowledge management: A case study in a building materials company - YILMAZ, YÜCEL (My University, 2007)
Purpose The purpose of this paper is to better understand knowledge management (KM) methods that can be carried out to determine the critical processes in that KM can provide important benefits. Design/methodology/approach In order to achieve this objective, a literature review was developed and a case study was applied in a building materials company in Turkey. Findings The results reflect that critical processes for KM can be determined in relation to four criteria. These are: value added, decision support, information-material intensity, and information amount. Originality/value The paper points out how KM methods can be implemented in organizations effectively. This article provides a frame which explains how knowledge-based process analyses can be applied. © 2007, Emerald Group Publishing Limited
Keywords: Function evaluation; Knowledge management; Knowledge processes; Turkey